ANALISIS PENGGUNAAN DIGITAL PAYMENT BERDASARKAN TECHNOLOGY ACCEPTENCE MODEL (TAM) PADA MAHASISWA UNIVERSITAS BUDI LUHUR - Ananta Nabilah Putri; Rizki Pratomo Sunarwibowo (Jurnal Nirta : Inovasi Multidisiplin, 2026)
The food packaging industry in Surabaya is marked by intense competition, necessitating effective marketing strategies to enhance customer satisfactionThis study aims to analyze the factors influencing students’ behavioral intention to use digital payment systems by applying an extended Technology Acceptance Model (TAM). The variables examined include subjective norms, computer self-efficacy, perceived enjoyment, perceived usefulness, and perceived ease of use. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 36, with 365 respondents who met the criteria as students of Universitas Budi Luhur selected as research samples. The data analysis technique used was Partial Least Square–Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.1.1.6. The results indicate that subjective norms have a positive and significant effect on perceived usefulness, while computer self-efficacy and perceived enjoyment have positive and significant effects on perceived ease of use. Furthermore, perceived usefulness and perceived ease of use significantly influence behavioral intention to use digital payment systems. The findings also reveal indirect effects through mediating variables. This study contributes theoretically to the development of the TAM framework and provides practical implications for digital payment service providers and educational institutions in enhancing digital payment adoption.